If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x+3 = 0
4*x+12 = 0
x+3 = 0
x+3 = 0
x+3 = 0 // - 3
x = -3
4*x+12 = 0
4*x+12 = 0
4*x+12 = 0 // - 12
4*x = -12 // : 4
x = -12/4
x = -3
x in (-oo:-3) U (-3:+oo)
2/(x+3)+3/8 = 5/(4*x+12) // - 5/(4*x+12)
2/(x+3)-(5/(4*x+12))+3/8 = 0
2/(x+3)-5*(4*x+12)^-1+3/8 = 0
2/(x+3)-5/(4*x+12)+3/8 = 0
(2*8*(4*x+12))/(8*(x+3)*(4*x+12))+(-5*8*(x+3))/(8*(x+3)*(4*x+12))+(3*(x+3)*(4*x+12))/(8*(x+3)*(4*x+12)) = 0
2*8*(4*x+12)-5*8*(x+3)+3*(x+3)*(4*x+12) = 0
12*x^2+24*x+72*x+72+108 = 0
12*x^2+96*x+180 = 0
12*x^2+96*x+180 = 0
12*(x^2+8*x+15) = 0
x^2+8*x+15 = 0
DELTA = 8^2-(1*4*15)
DELTA = 4
DELTA > 0
x = (4^(1/2)-8)/(1*2) or x = (-4^(1/2)-8)/(1*2)
x = -3 or x = -5
12*(x+5)*(x+3) = 0
(12*(x+5)*(x+3))/(8*(x+3)*(4*x+12)) = 0
(12*(x+5)*(x+3))/(8*(x+3)*(4*x+12)) = 0 // * 8*(x+3)*(4*x+12)
12*(x+5)*(x+3) = 0
( x+3 )
x+3 = 0 // - 3
x = -3
( x+5 )
x+5 = 0 // - 5
x = -5
x in { -3}
x = -5
| 26=x+8 | | 13+3x+166=180 | | 8x-x=28 | | 2s-8=-7+3s | | 3(w+2)-2(w-1)+5= | | 8x-x=28 | | 2s-8=-7+3s | | 10x^2-20x=30 | | x-6/11=6/11 | | x-6/11=6/11 | | 7(t-5)+8t=5(3t+5)-9 | | 6m-23=-23+5m | | T^2+8x-8=0 | | 5(2-4d)-6d=8d-126 | | -(6y+4)-(5y-8)=1 | | 2(3+3x)-3=21 | | 56-9x=-x-64 | | s(t)=-16t^2+48t+64 | | -3(3x+4)+5x+1=25 | | 2r-2=38+7r | | -3(3x+4)+5x+2=25 | | 21=7-2x | | 6x-19=5+3x | | 18=0.3x | | 8a^2+31a-4=0 | | 9y^2-16x^2+54y+128x-319=0 | | -9+69=-2x-133 | | 5(-4x+1)+x-5=-76 | | 4(t-5)+2=t | | 36-42x=42x+48 | | 15/3=x/12 | | 2(3+2x)-1=29 |